Pengaruh BAP terhadap Induksi Tunas Aglonema (Aglonema commutatum Schott.) - Didik Pudji Restanto; Amanda Intania; Wahyu Indra Duwi Fanata; Ahmad Ilham Tanzil; Mohammad Candra Prayoga (BPFP Universitas Bengkulu, 2024)
[EFFECT OF BENZYL AMINO PURIN ON SHOOT INDUCTION OF AGLONEMA (Aglonema commutatum Schott.)]. The Aglonema is a well-known ornamental plant and has a high selling value in Indonesia. It is characterized by attractive and beautiful leaves because of its diversity of colors and motifs. The Aglonema commutatum Schott plant is a type of Aglonema which is characterized by green leaves with white markings. The increasing demand for Aglaonema, both imports and exports, makes it impossible to propagate through seeds and cuttings, so it is important to optimize propagation through effective tissue culture. The aim of research was to determine effect of various concentrations of the BAP Benzyl Amino Purin on the shoot induction of A. commutatum plants. The explants used were the stem nodal parts which were planted in Murashige and Skoog media. The research design used CRD with a BAP concentration factor consisting of 6 levels, namely 0 mg/L, 4 mg/L, 8 mg/L, 12 mg/L, 16 mg/L and 20 mg/L. The BAP concentration treatment showed a very significant different effect on the induction of A. commutatum tuna. The 8 mg/L BAP treatment showed the best results with the fastest initial explant response 10.8 dap, the highest number of shoots was 2 shoots/elplant, and the highest shoot was 0.75 cm.